The Effectiveness of STEM-Based Guided Inquiry Learning to Train Science Literacy of Physics - Vichi Cahyo Eko Saputro; Wasis; Tjipto Prastowo (Indonesia Approach Education, 2022)
This study aims to determine the effectiveness of STEM-based guided inquiry learning on physics science literacy. This study uses a research and development (R & D) development model with a one group pretest-posttest design. The sample used was class XI students with three replications. The data collection technique is in the form of a science literacy test sheet. Then analyzed with a quantitative and qualitative descriptive approach. The research data shows that the learning model developed is theoretically valid by three expert validators. The effectiveness of learning tools is shown by the science literacy scores of students who have increased after applying the STEM-based guided inquiry learning model. Based on the discussion of the research results, it can be concluded that the learning tools developed are effectively applied in schools to train students' science literacy in sound wave material.